The effects of photocatalytic activity with titanium dioxide on the performance and emission characteristics of SI engine. (April 2021) - Kapusuz, Murat; Gurbuz, Mevlut; Ozcan, Hakan
Highlights: The photocatalysis has no effect on standard gasoline. Practice of photocatalysis to E15 reduces HC and CO emissions. Photocatalysis provides conversion to alcohol, alkanes and ethers. Engine performance increases in case of photocatalysis application to E15. Photocatalysis application increases CO2 and emissions. Abstract: This study aimed to improve the properties of gasoline fuel with the help of the photocatalysis method. Accordingly, a 100 ml volume photocapsule was designed and manufactured. UV radiation was applied on gasoline in the photocapsule. If no reductor is used, no change can be obtained. When water was mixed with the fuel, the changes were below the experimental error. However, in the case of ethanol mixing there have been significant improvements in terms of combustion. Distillation test and FTIR analysis were applied to the fuel samples. As a result of FTIR analysis, it was determined that the alcohol content increased and the fuel storage life was extended. The experiments were carried out for constant throttle opening as 4 speed in the range of 1200–1800 rpm (200 rpm increments) for performance and emissions of the engine. As a result of photocatalysis; unification, conversion to alkane, ether, and alcohol groups were determined. Photocatalysis reduces the emissions of HC and CO by a ratio of 6.68% and 20.5% on average and increases the emissions of CO2 emissions and NOX by a ratio of 19.9% and 34.8% respectively. On the other hand, this method reduces BSFC by a ratio of 9% and increases BTE by a ratio of 10% on average. This research proves that photocatalysis can be used with an improving effect on hydrocarbon mixtures.